Evaluation of the Drainage System in Kotabaru Village, West Bekasi, Using the EPA SWMM Model - Armawan, Ladynda Maghfira Aulia; Pribadi, Andik (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
The Kotabaru Village in West Bekasi District, Bekasi City, frequently experiences flooding. Flood events in this area have even reached depths of 100 cm. These events disrupt residents' activities and force them to evacuate. An evaluation of the drainage channels is necessary to identify the causes of flooding and develop solutions. This study aims to analyze the causes of flooding and provide recommendations for flood management based on simulations using EPA SWMM 5.2 software. The data used in this study include daily rainfall data from the GPM (Global Precipitation Measurement) satellite for the period 2013-2022, a contour map of Bekasi City, and a land cover map. Hydrological analysis methods and modeling using EPA SWMM 5.2 are employed to identify flood points and accurately calculate the capacity of the drainage channels. The hydrological analysis results show that rainfall in this area follows a Log-Pearson Type III distribution. The design rainfall with a 5-year return period is 267.87 mm. The SWMM model involves 30 subcatchments, 126 junctions, 168 conduits, and 1 outfall. A 24-hour simulation indicates that 5 channels are highlighted in red, meaning their capacity is insufficient, and the channel profiles show overflows due to flow queuing towards the Cakung River. Capacity analysis shows that the simulated discharge under existing conditions reaches 44.01 m³/s. After improvements, the Cakung River and the residential drainage channels function properly without any overflows.